Blindspots in Economics and Design: A Review of John Heskett’s Design and the Creation of Value - Sharon Helmer Poggenpohl (She Ji: The Journal of Design, Economics and Innovation, 2017)
Blindspots in Economics and Design is a review of John Heskett’s Design and the Creation of Value (2017). Importantly, the book cogently examines five economic theories and presents diagrammatic interpretation of their foci, contrasts, and evolutions. Building on previous diagrams, a proposed Value Creation Theory visually locates design in the economic-business context. Blindspots are identified with reference to how design perceives economics, and the converse, how economics perceives design. Shortcomings in design education are discussed with regard to economics, business, and the rapidly changing technological context in which we live and work. Emerging economic theory that overlaps economics and psychology, behavioral economics, may offer insight and the possibility of collaborative investigation to more securely locate the economic contribution of design. Keywords: Economics and design, Economic theory, Value conflicts, Design education limitations